TRIM21 is critical for survival of Toxoplasma gondii infection and localises to GBP-positive parasite vacuoles - Clémence Foltz; Anna Napolitano; Rabia Khan; Barbara Clough; Elizabeth M. Hirst; Eva-Maria Frickel (Scientific Reports, 2017)
Abstract Interferon gamma (IFNγ) is the major proinflammatory cytokine conferring resistance to the intracellular vacuolar pathogen Toxoplasma gondii by inducing the destruction of the parasitophorous vacuole (PV). We previously identified TRIM21 as an IFNγ-driven E3 ubiquitin ligase mediating the deposition of ubiquitin around pathogen inclusions. Here, we show that TRIM21 knockout mice were highly susceptible to Toxoplasma infection, exhibiting decreased levels of serum inflammatory cytokines and higher parasite burden in the peritoneum and brain. We demonstrate that IFNγ drives recruitment of TRIM21 to GBP1-positive Toxoplasma vacuoles, leading to Lys63-linked ubiquitination of the vacuole and restriction of parasite early replication without interfering with vacuolar disruption. As seen in vivo, TRIM21 impacted the secretion of inflammatory cytokines. This study identifies TRIM21 as a previously unknown modulator of Toxoplasma gondii resistance in vivo thereby extending host innate immune recognition of eukaryotic pathogens to include E3 ubiquitin ligases.